Robotic Arch Catheter Placement Reduces Cerebral Embolization During Thoracic Endovascular Aortic Repair (TEVAR). (March 2017) - Perera, A.H.; Riga, C.V.; Monzon, L.; Gibbs, R.G.; Bicknell, C.D.; Hamady, M.
Abstract : Objective: Stroke caused by cerebral embolization constitutes a principal risk during arch manipulation and thoracic endovascular aortic repair (TEVAR). This study investigates the incidence of cerebral embolization during catheter placement in the aortic arch, and compares robotic and manual techniques. Methods: Intra-operative transcranial Doppler (TCD) was performed in 11 patients undergoing TEVAR. Wire and catheter placement in the arch was performed by two experienced operators. Manual and robotic catheter placement and removal were compared for each patient; 44 manoeuvres were studied in total. A conventional 5Fr pigtail catheter was used for manual cannulation via a 5Fr access sheath. The 6Fr/9Fr co-axial Magellan endovascular robotic system was used for robotic navigation operated from a remote workstation. The number of high intensity transient signals (HITS) detected by TCD during different stages of TEVAR was recorded. Results: The median procedural embolization rate was 173 (interquartile range 97–240). There were significantly fewer HITS detected during robotic catheter placement with six in total (median 0, IQR 0–1), compared with 38 HITS (median 2, IQR 1–5) during manual catheter placement ( p = .018). There were no HITS detected during robotic catheter removal by auto-retraction as per manufacturer instructions. On two occasions, however, when the robotic catheter system was removed manually without correcting for articulation, it resulted in one HIT in one case and 11 HITS in the second case. Conclusions: Robotic catheter placement is feasible during TEVAR, and results in significantly less cerebral embolization compared with manual techniques. The active manoeuvrability, control, and stability of the robotic system is likely to reduce contact with an atheromatous aortic arch wall, and thereby reduce dislodgement of particulate matter and result in less embolization. The importance of adhering to manufacturer instructions during use and removal of the robotic catheter is also highlighted.